1274. Activity of Ceftolozane/Tazobactam, Imipenem/Relebactam, and Comparators Against Pseudomonas aeruginosa Isolates from Patients with Bloodstream and Other Infection Types—SMART United States/Canada 2018-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Andrew DeRyke, C; Harris, Kelly; Young, Katherine; Motyl, Mary; Sahm, Daniel F
Abstract: Background: Ceftolozane/tazobactam (C/T), an antipseudomonal cephalosporin combined with a β-lactamase inhibitor, was approved for treatment of complicated urinary tract (cUTI) and intraabdominal infections (cIAI), and hospital-acquired/ventilator-associated bacterial pneumonia (HAP/VAP). Imipenem/relebactam (IMI/REL) is a combination of imipenem/cilastatin with relebactam, an inhibitor of class A and C β-lactamases. IMI/REL was approved for HAP/VAP and for infections due to aerobic gram-negative organisms in adults with limited treatment options (e.g., cUTI, cIAI). We compared the activity of C/T and IMI/REL against P. aeruginosa from bloodstream infections (BSI) to those from other infection types. Methods: As part of the SMART program, 24 hospitals in the US and 8 in Canada each collected up to 250 consecutive gram-negative isolates per year in 2018-2019 from patients with BSI, lower respiratory tract infections (LRTI), IAI, and UTI. A total of 2351 Pa isolates were collected. MICs were determined using CLSI broth microdilution and breakpoints. Results: Pa isolates from BSI tended to show higher susceptibility than IAI, UTI, and especially LRTI isolates (Table). Susceptibility to the tested comparator β-lactams was 11-12 percentage points lower among LRTI than BSI isolates, while C/T and IMI/REL susceptibility was only 2-5% lower. Even among BSI isolates, the comparator β-lactams were active against only 75-88% of isolates, while C/T and IMI/REL were active against >95%. Only amikacin showed higher activity. Analyzing coverage by either C/T or IMI/REL, 98.7% of Pa isolates from BSI were susceptible to one or both agents. C/T and IMI/REL maintained activity against 89% and 69% of meropenem-nonsusceptible (MEM-NS) Pa isolates from BSI (n=36), respectively, and 87% and 76% of piperacillin/tazobactam (P/T)-NS Pa (n=38). Results Table Conclusion: Even among BSI isolates, which were generally more susceptible than those from other infection types, Pa susceptibility to commonly used β-lactams like MEM and P/T was < 90%, 7-23% lower than C/T and IMI/REL. Given the desirability of β-lactams among clinicians and the >98% coverage by either C/T or IMI/REL of Pa isolates from BSI, both agents represent important options in the treatment of patients with BSI. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) C. Andrew DeRyke, PharmD, Merck & Co., Inc. (Employee, Shareholder) Kelly Harris, PharmD, BCPS, Merck & Co. Inc (Employee) Katherine Young, MS, Merck (Employee) Mary Motyl, PhD, Merck & Co., Inc. (Employee, Shareholder) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)